JIHAD MANAGEMENT IS THE NECESSITY OF TRANSFORMATION IN BANKING SYSTEM (Singaporean Journal of Business Economics and Management, 2014)
Country's banking system has had an important role in improving the efficiency of economic environment, business and production development. Banking system predisposes the economic growth of the country. In accordance with the Banks' role in welfare and national development, evaluating their performance and the effective factors on their efficiency is so important. Therefore, determining the effective factors and methods on the efficiency of banking system can play an effective role in national development. In this regard, the concept of Jihad Management as a practical and theoretical paradigm can be a new and effective strategy in enhancing banking system efficiency. The purpose of this research is to investigate the role of jihad management in enhancing banking system efficiency. Because of the wide range of related concepts to jihad management and the closeness of the concept of organizational citizenship behavior to jihad management, at first the related concepts to organizational citizenship behavior are studied and then some recommendations for the use of jihad management in the direction of improving banking system were presented.